Magneto-optical spectroscopy of magnetic multilayers: Theory and experiment (A review) - Antonov, V.N.; Uba, L.; Uba, S.; Yaresko, A. N.; Perlov, A. Ya.; Nemoshkalenko, V.V. (Физика низких температур, 2001)
Experimental and theoretical results on the optical and magneto-optical (MO) spectral properties of a series of Co/Cu, Co/Pd, Co/Pt and Fe/Au multilayers (MLS) are reviewed. Diagonal and off-diagonal components of the optical conductivity tensor have been determined in the photon energy range 0.8-5.5 eV from the polar and longitudinal Kerr rotation as well as ellipticity and the ellipsometry measurements. The conductivity tensor has been evaluated on the basis of self-consistent spin-polarized relativistic linear muffintin orbital (LMTO) band-structure calculations within the local spin-density approximation. The role of the spin polarization and the spin-orbit interaction in the formation of the magneto-optical Kerr effect (MOKE) spectra as inferred from first-principles calculations is examined and discussed. The high sensitivity of the MO properties to the interface structure is studied by ab initio modeling of the effects of the interface alloying, substitutional disorder, and the roughness at the interfaces. It is shown that the MOKE spectra of the MLS calculated using the LMTO method reproduce the experimental spectra only moderately well if ideal multilayer structure with sharp interfaces are assumed. It is shown that the MOKE spectra of the MLS can be adequately reproduced only by taking into account their real interface microstructure. The magneto-optical anisotropy (MOA) is studied both experimentally and theoretically for a series of Fen/Aun superlattices prepared by molecular beam epitaxy with n=1,2,3 of Fe and Au atomic planes of (001)orientation. The results of the LMTO calculations show that the microscopic origin of the large MOA is the interplay of the strong spin- orbit coupling on Au sites and the large exchange splitting on Fe sites via Au d-Fe d hybridization of the electronic states at the interfaces. The orientation anisotropy of the d orbital moment is calculated from first principles and analyzed on the basis of d orbital symmetry considerations. The relationship between the orbital moment anisotropy and the MOA is discussed. The reviewed results imply that the magneto-optical properties of multilayers with various compositions and structures can be quantitatively predicted from first-principles band-structure calculations. Such a possibility is important for basic research as well aplications.

Experimental and theoretical results on the optical and magnetooptical (MO) spectral properties of a series of Co/Cu, Co/Pd, Co/Pt and Fe/Au multilayers are reviewed. Diagonal and off-diagonal components of the optical conductivity tensor have been determined in the photon energy range 0.8-5.5 eV from the polar and longitudinal Kerr rotation as well as ellipticity and ellipsometry measurements. The conductivity tensor has been evaluated on the basis of self-consistent spin-polarized relativistic linear muffin-tin orbital (LMTO) band-structure calculations within the local spin-density approximation. The role of the spin polarization and the spin–orbit interaction in the formation of the magnetooptical Kerr effect (MOKE) spectra as inferred from first-principles calculations is examined and discussed. The high sensitivity of the MO properties to the interface structure is studied by ab initio modeling of the effects of the interfacial alloying, substitutional disorder, and the roughness at the interfaces. It is shown that the MOKE spectra of the multilayered structures (MLS) calculated using the LMTO method reproduce the experimental spectra only moderately well if ideal MLS with sharp interfaces are assumed. It is shown that the MOKE spectra of the MLS can be adequately reproduced only by taking into account their real interface microstructure. The magnetooptical anisotropy (MOA) is studied both experimentally and theoretically for a series of Fen/Aun superlattices prepared by molecular beam epitaxy with n=1,2,3 Fe and Au atomic planes of (001) orientation. The results of the LMTO calculations show that the microscopic origin of the large MOA is the interplay of the strong spin-orbit coupling on Au sites and the large exchange splitting on Fe sites via Aud–Fe d hybridization of the electronic states at the interfaces. The orientation anisotropy of the d orbital moment is calculated from first principles and analyzed on the basis of d orbital symmetry considerations. The relationship between the orbital moment anisotropy and the MOA is discussed. The reviewed results imply that the magnetooptical properties of multilayers with various compositions and structures can be quantitatively predicted from first-principles band-structure calculations. Such a possibility is important for basic research as well as applications.